2008
DOI: 10.1111/j.1365-2486.2008.01605.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in grassland ecosystem function due to extreme rainfall events: implications for responses to climate change

Abstract: Climate change is causing measurable changes in rainfall patterns, and will likely cause increases in extreme rainfall events, with uncertain implications for key processes in ecosystem function and carbon cycling. We examined how variation in rainfall total quantity (Q), the interval between rainfall events (I), and individual event size (S E ) affected soil water content (SWC) and three aspects of ecosystem function: leaf photosynthetic carbon gain (A CO2 ), aboveground net primary productivity (ANPP), and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
167
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(181 citation statements)
references
References 31 publications
(49 reference statements)
13
167
1
Order By: Relevance
“…However, only drought impacts translated to changes in growth rates and propagated to impacts in higher order ecological processes to individuals that do not produce detectable impacts on plant population or community composition and ecosystem productivity [49,50]. For example, despite evidence of widespread tissue dieback in individuals, Kreyling et al [49] observed plant community productivity to be unaffected by both drought and heavy precipitation events.…”
Section: Scaling Individual Plant Responses To the Population And Commentioning
confidence: 99%
“…However, only drought impacts translated to changes in growth rates and propagated to impacts in higher order ecological processes to individuals that do not produce detectable impacts on plant population or community composition and ecosystem productivity [49,50]. For example, despite evidence of widespread tissue dieback in individuals, Kreyling et al [49] observed plant community productivity to be unaffected by both drought and heavy precipitation events.…”
Section: Scaling Individual Plant Responses To the Population And Commentioning
confidence: 99%
“…Studies in a mesic grassland have previously observed a decrease in both leaf photosynthetic carbon gain and soil respiration as a result of more intermittent rainfall patterns Fay et al, 2002;Harper et al, 2005), while Fay et al (2008) reported increases in leaf-level photosynthesis and decreases in soil respiration due to increased rainfall event size for levels of total rainfall ranging from 400 to 1000 mm yr −1 . These studies did not provide information concerning the relative sensitivity of these individual processes to variations in rainfall pattern, so it is not possible to reconstruct the dependence of overall ecosystem carbon flux on precipitation frequency for these sites.…”
Section: Differential Ecosystem Flux Responsesmentioning
confidence: 99%
“…In parallel to climate change, environmental nitrogen (N) inputs resulting from anthropogenic activities is changing the N cycle in terrestrial ecosystems (Vitousek et al, 1997;Cui et al, 2013), affecting ecosystem processes (Phoenix et al, 2012;. Despite global change drivers are known to interact in their impacts on ecosystem services, we have limited knowledge on how the interaction between important factors such as decreasing rainfall frequency and increasing N inputs will affect ecosystem functioning in drylands (e. g. N cycle) and influence microbial communities; which carry out vital ecosystem functions (Fay et al, 2008;Delgado-Baquerizo et al, 2014). In drylands, water and N are the most important factors limiting resources for plant and microbial activity (Hooper and Johnson, 1999;Austin, 2011).…”
Section: Introductionmentioning
confidence: 99%